Evaluating first-line therapeutic strategies for metastatic castration-resistant prostate cancer: a comprehensive network meta-analysis and systematic review - Zhang, Duojie; Weng, Haimin; Zhu, Zhangji; Gong, Weilun; Ma, Yinfeng (Frontiers in Oncology, 2024)
Objective This study aimed to evaluate the relative efficacy and safety of first-line treatment options for metastatic castration-resistant prostate cancer (mCRPC).We systematically searched electronic databases, including PubMed and Web of Science, for studies published from their inception to April 3rd, 2023.Inclusion criteria were: 1) Completed Phase III or IV randomized controlled trials (RCTs) registered on ClinicalTrials.gov; 2) Patients with a confirmed diagnosis of mCRPC who had not previously received chemotherapy or novel endocrine therapies.We conducted a network meta-analysis using R software (version 3.4.0). Network graphs and risk of bias graphs were generated using Stata 14.0 and RevMan 5.4, respectively. The primary outcome was overall survival (OS), and the secondary outcome was the incidence of severe adverse events (SAEs). Results Seven RCTs encompassing 6,641 patients were included. The network meta-analysis revealed that both docetaxel+prednisone (DP) and cabazitaxel+prednisone (CP) significantly improved OS compared to abiraterone. Compared to placebo, DP showed comparable results to both cabazitaxel 20 mg/m ^2+prednisone (C20P) and cabazitaxel 25 mg/m ^2+prednisone (C25P) in terms of OS. For SAEs, both DP and C20P were superior to C25P, with no statistical difference between C20P and DP. The probability ranking plots indicated that C25P ranked highest for OS, while DP ranked highest for SAEs. Conclusions Based on our network meta-analysis, we recommend cabazitaxel 20 mg/m ^2+prednisone (C20P) as the primary choice for first-line management of mCRPC, followed by DP. Enzalutamide and abiraterone are suggested as subsequent options. Radium-223 may be considered for patients presenting with bone metastases.